Pheochromocytoma Crisis in the ICU: A French Multicenter Cohort Study With Emphasis on Rescue Extracorporeal Membrane Oxygenation. Issue 7 (July 2017) - Sauneuf, Bertrand; Chudeau, Nicolas; Champigneulle, Benoit; Bouffard, Claire; Antona, Marion; Pichon, Nicolas; Marrache, David; Sonneville, Romain; Marchalot, Antoine; Welsch, Camille; Kimmoun, Antoine; Bouchet, Bruno; et al.
Abstract : Objectives: To describe the characteristics, management, and outcome of patients admitted to ICUs for pheochromocytoma crisis. Design: A 16-year multicenter retrospective study. Setting: Fifteen university and nonuniversity ICUs in France. Patients: Patients admitted in ICU for pheochromocytoma crisis. Interventions: None. Measurement and Main Results: We included 34 patients with a median age of 46 years (40–54 yr); 65% were males. At admission, the median Sequential Organ Failure Assessment score was 8 (4–12) and median Simplified Acute Physiology Score II 49.5 (27–70). The left ventricular ejection fraction was consistently decreased with a median value of 30% (15–40%). Mechanical ventilation was required in 23 patients, mainly because of congestive heart failure. Vasoactive drugs were used in 23 patients (68%) and renal replacement therapy in eight patients (24%). Extracorporeal membrane oxygenation was used as a rescue therapy in 14 patients (41%). Pheochromocytoma was diagnosed by CT in 33 of 34 patients. When assayed, urinary metanephrine and catecholamine levels were consistently elevated. Five patients underwent urgent surgery, including two during extracorporeal membrane oxygenation. Overall ICU mortality was 24% (8/34), and overall 90-day mortality was 27% (9/34). Crude 90-day mortality was not significantly different between patients managed with versus without extracorporeal membrane oxygenation (22% vs 30%) ( p = 0.7) despite higher severity scores at admission in the extracorporeal membrane oxygenation group. Conclusions: Mortality is high in pheochromocytoma crisis. Routinely considering this diagnosis and performing abdominal CT in patients with unexplained cardiogenic shock may allow an earlier diagnosis. Extracorporeal membrane oxygenation and adrenalectomy should be considered as a therapeutic in most severe cases.